Anaphylactic reaction/angioedema associated with jellyfish sting - Campos Pereira, Joao Claudio (2018)
The most frequent jellyfish in Southern Brazil causes mainly local pain and skin plaques. A 3-year-old female bather presented an erythematous, irregular plaque on the left forearm after contact with a jellyfish and intense facial angioedema with facial flushing. The lungs had vesicular murmur, wheezes, and snorts, and pink and spumous secretion in the airways with intercostal retraction. She was administered subcutaneous adrenaline (0,01mg/kg) and hydrocortisone intravenous (10mg/kg) with total recovery in a few minutes. The manifestations of anaphylactic reactions are distinct from those of envenomations, and prompt and adequate care is fundamental in these situations.